Hungry children age faster - Ana Lucia Abeliansky; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
We analyze how childhood hunger affects human aging for a panel of European individuals. For this purpose, we use six waves of the Survey of Health, Aging, and Retirement in Europe (SHARE) dataset and construct a health deficit index. Results from log-linear regressions suggest that, on average, elderly European men and women developed about 20 percent more health deficits when they experienced a hunger episode in their childhood. The effect becomes larger when the hunger episode is experienced earlier in childhood. In non-linear regressions (akin to the Gompertz-Makeham law), we obtain greater effects suggesting that health deficits in old age are up to 40 percent higher for children suffering from hunger. The wedge of health deficits between hungry and and non-hungry individuals increases absolutely and relatively with age. This implies that individuals who suffered from hunger as children age faster.
Keywords: I10; I19; J13; 330; health; aging; health deficit index; hunger episodes; childhood health